Manual for performance trials of forage and pasture crops (Book series, 1991)
This publication details the criteria and guidelines to be followed in the performance testing and evaluation of forage and pasture crops. It includes guidelines and basic and advanced experimental procedures for grasses and legumes. The whole manual is a product of the consultation workshops participated by researchers from different agencies who are actively engaged in these activities. The authors aim for this publication to be a standardized guide to improve the effectiveness of the comparison of performance evaluations (of forage and pasture) under different agroclimatic conditions.